Glucose-lowering drugs in patients with chronic kidney disease: a narrative review on pharmacokinetic properties - Arnouts, P.; Bolignano, D.; Nistor, I.; Bilo, H.; Gnudi, L.; Heaf, J.; Biesen, W. v. (Nephrology, dialysis, transplantation, 2014)
The achievement of a good glycaemic control is one of the cornerstones for preventing and delaying progression of microvascular and macrovascular complications in patients with both diabetes and chronic kidney disease (CKD). As for other drugs, the presence of an impaired renal function may significantly affect pharmacokinetics of the majority of glucose-lowering agents, thus exposing diabetic CKD patients to a higher risk of side effects, mainly hypoglycaemic episodes. As a consequence, a reduction in dosing and/or frequency of administration is necessary to keep a satisfactory efficacy/safety profile. In this review, we aim to summarize the pharmacology of the most widely used glucose-lowering agents, discuss whether and how it is altered by a reduced renal function, and the recommendations that can be made for their use in patients with different degrees of CKD.